Corrosion resistance of functionally graded TiN/Ti coatings for proton exchange membrane fuel cells. (27th November 2020) - Silva, F.C.; Prada Ramirez, O.M.; Tunes, M.A.; Edmondson, P.D.; Sagás, J.C.; Fontana, L.C.; de Melo, H.G.; Schön, C.G.
Abstract: Bipolar Plates (BPP) are important components of proton exchange membrane fuel cell (PEMFC) stacks. In the development of innovative fuel cell designs, it is advantageous to use aluminum for these applications, however, this material lacks the necessary corrosion resistance. Since the performance of PEMFC stacks depends on BPP properties, in particular, corrosion resistance, depositing titanium nitride (TiN) thin films onto aluminum substrates may improve their efficiency and durability. The present work focuses on improving corrosion resistance and hydrophobicity of TiN/Ti by using N graded films deposited onto aluminum substrates (AA-1100) by grid-assisted magnetron sputtering (GAMS). Electrochemical impedance spectroscopy (EIS) and potentiodynamic and potentiostatic polarization are used to investigate the performance of the substrate/film system at room temperature and 70 °C, thus simulating a prototypic PEMFC electrolyte environment. Electrochemical test results showed that graded TiN films improved corrosion resistance when compared with both the homogeneous films and the AA1100 uncoated substrate. Furthermore, contact angle results reveal improved hydrophobicity for both homogeneous and graded TiN coatings when compared with the AA1100 substrate. Highlights: Graded and homogeneous TiN/Ti films were deposited on AA-1100 substrates by GAMS. TiN/Ti films shows better corrosion resistance than the uncoated substrate. Contact angle results of TiN/Ti films was greater than substrates uncoated. Graded TiN/Ti films outperforms the corrosion resistance of homogeneous TiN/Ti films. Graded TiN/Ti films can be successfully applied to bipolar plates surface.